2016
DOI: 10.1016/j.jhin.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Successful control of an outbreak of GES-5 extended-spectrum β-lactamase-producing Pseudomonas aeruginosa in a long-term care facility in Japan

Abstract: An outbreak of MDRP with an antimicrobial resistance gene, blaGES-5, occurred in a Japanese LTCF. It was successfully controlled by enhanced infection control measures, which neighbouring hospitals and a local public health centre supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…The quality of 20 studies was assessed and the results are summarized in Fig 2. One study was at high risk for five criteria [14]. Six studies were at low risk for all criteria [15][16][17][18][19][20]. Problems related to recall bias and standardization of self-reported measurement created a high risk of bias for the measurement of the exposure domain in seven studies [14,[21][22][23][24][25][26].…”
Section: Risk Of Bias In the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The quality of 20 studies was assessed and the results are summarized in Fig 2. One study was at high risk for five criteria [14]. Six studies were at low risk for all criteria [15][16][17][18][19][20]. Problems related to recall bias and standardization of self-reported measurement created a high risk of bias for the measurement of the exposure domain in seven studies [14,[21][22][23][24][25][26].…”
Section: Risk Of Bias In the Included Studiesmentioning
confidence: 99%
“…Three reports of GAS outbreaks found lapses in wound care practice such as inconsistent cleaning and disinfection [20,37,38]. The outbreaks of MDROs and hepatitis B reported device related issues including sharing of a device and inappropriate use of reusable devices [15,18,21,34]. Hepatitis B and C outbreaks commonly reported that lapses during podiatry care and point-of-care testing procedures (blood glucose test and international normalized ratio monitoring) caused the transmission of bloodborne pathogens among residents [18,19,21,28,30].…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations